Improving the biopharmaceutical performance of azole antifungals: a comparative study of solid dispersion and co-crystallization of ketoconazole and itraconazole - Payal Dasgupta; Bipul Nath; Apurba Talukdar; Atanu Sarma; Sidhartha Jyoti Bora (Creative Pharma Assent, 2026)
Background: Oral bioavailability of BCS class II azole antifungals, ketoconazole and itraconazole, is hampered by low aqueous solubility. Improving solubility and dissolution is necessary for greater therapeutic efficacy. This research compared two approaches: solid dispersion and pharmaceutical co-crystallization to improve their biopharmaceutical properties. Methodology: Solid dispersions were prepared using the organic solvent evaporation technique with PEG-10000 for ketoconazole and HPMCE50 for itraconazole. Co-crystals with benzoic and tartaric acids were studied by FT-IR, DSC, and PXRD. Optimized formulations were compressed into tablets and analyzed for pharmacopoeial parameters, dissolution, release kinetics, and ICH stability. Results and Discussion: Saturation solubility investigations revealed that, compared to amorphization, solid dispersions exhibited more efficient enhancement due to the combined effect of amorphous enrichment and polymer solubilization. Tartaric acid co-crystals could increase solubility by crystal lattice modification. cc-Tabs showed burst release profiles, while SDs gave controlled drug release. The release of drug was in accordance with the first-order and Korsmeyer–Peppas models with anomalous transport, and was sustained for six months. The low aqueous solubility of azole antifungals restricts their oral bioavailability. The solubility and dissolution of ketoconazole and itraconazole were enhanced by solid dispersion and co-crystallization. Solid dispersions provided superior amorphous stability and extended-release, while co-crystals led to faster initial dissolution and better early drug availability. Conclusion: Both approaches were successful in improving solubility, dissolution, and stability. Both SDs modulated drug release kinetics; sustained-release profiles were obtained from the solid dispersions, and fast dissolution was favored by co-crystallization, thus providing both as viable approaches for oral delivery of poorly soluble azole antifungals.